Difficult texts: the Christology of the Centurion's words in Luke 23.47. Issue 3 (May 2022) - James, Rob
The words uttered by the Centurion present at the death of Jesus in Luke's Gospel represent a deliberate change to Luke's inherited material. The choice of whether to understand the key word in Luke's phrasing as 'innocent' or 'righteous' has huge implications for the weight which we might give to this rephrased exclamation. It is suggested that Luke intended this word to be understood as 'righteous'. Understood in this way, the Centurion's words become a Christological statement about the divinity that is present in Jesus.